2015
DOI: 10.1007/s11738-015-1983-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro slow growth storage of Senecio macrophyllus shoots

Abstract: Advances in biotechnology, especially in the field of in vitro culture techniques, led to the development of procedures that can be used as an excellent tool in plant conservation. The present study describes in vitro conservation of Senecio macrophyllus by slow-growth storage. Various sugar treatments, concentration of abscisic acid (ABA), light intensity and type of containers were tested. Viability and proliferation rate of shoots were evaluated 4 weeks after regrowth. The results obtained showed that polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Our results showed that the conservation period has a significant effect on the percentage of cultures vitality in the laboratory to maintain the ability to multiply and rooting, as this effect varied according to the strength of medium, as it was noticed that the conservation period of 3 and 6 months had good results, if compared to the 9-month conservation period, and with the increase in the conservation period to 9 months, the viability percentage and ability to multiply and rooting decreased. These results are in line with what Trejgell et al (2015) found when storing Senecio macrophyllus shoots in vitro for three and six months.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the conservation period has a significant effect on the percentage of cultures vitality in the laboratory to maintain the ability to multiply and rooting, as this effect varied according to the strength of medium, as it was noticed that the conservation period of 3 and 6 months had good results, if compared to the 9-month conservation period, and with the increase in the conservation period to 9 months, the viability percentage and ability to multiply and rooting decreased. These results are in line with what Trejgell et al (2015) found when storing Senecio macrophyllus shoots in vitro for three and six months.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained for the shoots of Pyrus genotypes where incubation at low temperature and light intensity resulted in yellowing of shoots, leaf size became very small but the shoot tips were quite fresh and green (Ahmed et al 2010). In our previous studies on the storage of Senecio macrophyllus light also had a negative effect on shoots condition during storage, and addition of ABA to the medium improved their condition (Trejgell et al 2015). Poplar shoots were in better condition after storage in the dark than under light (Hausman et al 1994).…”
Section: Discussionmentioning
confidence: 83%
“…The visual rating of the stored shoots was evaluated directly after cold treatment. Shoots were rated on the scale from 0 to 5, on the basis of plant appearance (modified scale from Reed 1992, for details see Trejgell et al 2015). Shoot tips from converted plants were transferred on fresh MS medium with full-strength nutrients supplemented with 3% sucrose, 1.11 μM BA, 0.14 μM NAA and 0.8% agar in optimal growth conditions and subcultured twice.…”
Section: Post-storage Regrowthmentioning
confidence: 99%